Specificity of serum amyloid A as a biomarker of idiopathic pulmonary fibrosis. Issue 12 (22nd December 2020) - Vietri, Lucia; d'Alessandro, Miriana; Bergantini, Laura; Carleo, Alfonso; Cameli, Paolo; Mazzei, Maria Antonietta; Sestini, Piersante; Bargagli, Elena
Abstract: Serum amyloid A (SAA) is an apo‐lipoprotein produced by the liver in response to proinflammatory cytokines. Few data are available on SAA levels in patients with idiopathic pulmonary fibrosis (IPF), the most common idiopathic form of interstitial pneumonitis (ILD). This study compared SAA concentration in IPF patients to other ILD groups to explore its potential use as a clinical biomarker.